Self-Regulation Differences of Mathematics Education Students Reviewing From Gender - Hesty Marwani Siregar (Jurnal Mercumatika : Jurnal Penelitian Matematika dan Pendidikan Matematika, 2022)
This study aimed to determine the difference in self-regulation of students of Mathematics Education FKIP Riau University during online lectures regarding gender. The subjects of this study were students of Mathematics Education FKIP Riau University batch 2017, 2018, and 2019 as many as 30 students, with details of 15 male and 15 female students. To collect data in this study, the authors used a self-regulation questionnaire. After the self-regulation questionnaire is valid and reliable, the questionnaire is then distributed to students who are research subjects. The self-regulation score data was then processed using descriptive statistical techniques. The results of data processing are then interpreted for each gender. Next, to see if there is a difference in self-regulation between students who take online lectures between male and female students, a t-test is carried out. Based on the results obtained, it can be concluded that there is no significant difference in self-regulation between male and female students. As a follow-up, lecturers can provide equal treatment between male and female students to optimize self-regulation. However, if we look at each indicator, there are indicators of task strategy and seeking help that reach different score categories between male and female students.